ANALISIS KINERJA PROGRAM DESA MANDIRI PADA DESA TIPOLOGI DARATAN DAN RAWA DI KABUPATEN INDRAGIRI HILIR - Yusmini '; Syaiful Hadi (Indonesian Journal of Agricultural Economics, 2010)
The objectives of this research were to analyze and assess performance of Desa Mandiri programon infrastructure development activities for the land and swamp typology village in Inhil District.This research used logical framework analysis (Kerangka Kerja Logis/KKL). Research resultsshowed that the performance of infrastructure development is quite good and the planning andimplementation are reciprocal to achieve goals. Empowerment-based infrastructure developmenthas encouraged self-reliance and working together (gotong royong), and public institutionfunctioning. It resulted in higher physical realization than the plan (over achievement), so thereis eficiency in the use of development budget. The weaknesses are as follow: lack of programsocialization, allocation of funds which is based on even distribution, lack of coordination andsynergy with related institutions, low capacity of village resource management (LPM), weakguidance and lack of community involvement in supervision.